ANALISIS PENGARUH PENAMPANG FONDASI TERHADAP DAYA DUKUNG DAN PENURUNAN FONDASI TIANG PANCANG BANGUNAN SCADA - Raihanah Naura Jinan; Rena Misliniyati; Khairul Amri; Muharram Nur Fikri; Fepy Supriani (LPPM Universitas Negeri Jakarta, 2025)
Bengkulu is an area with the potential risk of the Mentawai Pagai Megathrust subduction earthquake; it is necessary to evaluate the bearing capacity and foundation settlement of the building. This study aims to analyse the influence of variations in dimensions and cross-sectional shapes on the bearing capacity and foundation settlement of the Scada building using the Poulos and Davis method, the Reese and Wright method, the Luciano Decourt method, and the finite element method. Based on the results of the Standard Penetration Test (SPT), the influence of variations in shape, namely square and circular, with dimensions of 300 mm, 400 mm, and 500 mm, as well as depths of 7m, 9m, 11m, and 13m, affects the bearing capacity and foundation settlement. The analysis was conducted by comparing the bearing capacity and settlement of pile foundations in the Scada building using various methods. The analysis results show that the bearing capacity, deflection magnitude, and smallest settlement are below the permitted settlement limit, i.e., less than 10% of the foundation dimensions. The comparison between static and numerical methods, or the Bearing Capacity Ratio (BCR) approaching 1, is more efficient and safer to use. In this analysis, the BCR value closest to 1 was obtained for a 500 mm foundation using the Reese and Wright method at a depth of 9 m, yielding a bearing capacity of 312.04 tonnes for a single pile and 207.69 tonnes for a pile group.